Pregnancy Termination Model for Fetal Anomaly According to Maqasid Shariah - Siti Khatijah Ismail; Zainab Mohd Shafie; Nadhiran Nordin; Rahimah Embong; Lukman Abdul Mutalib (Human Resource Management Academic Research Society, 2024)
Vol. 13, No. 6, 2023, Pg. 2126 – 2133